1968
DOI: 10.1590/s0037-86821968000100001
|View full text |Cite
|
Sign up to set email alerts
|

Estudos sôbre reservatórios e vectores silvestres do Trypanosoma cruzi. XXIV. Variação dos dados biométricos obtidos em amostras do T. cruzi isolados de casos humanos da Doença de Chagas

Abstract: INTRODUÇÃOEmbora os dados biométricos obtidos de tripanossomos sem elhantes ao T. cruzi, iso lados de animais, não sejam por si só su ficientes p ara a identificação daqueles tr i panossomos como o agente etiológico da doença de Chagas, tais dados têm sido usa dos como elementos indispensáveis p ara aquela identificação. Entre os dados bio métricos de m aior im portância destaca-se, além do comprimento total médio do p a ra sita, o índice nuclear médio.O estudo biométrico do T. cruzi foi ini ciado por Dias (7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

1972
1972
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
3
0
4
Order By: Relevance
“…In a recent study, Martins et al 26 suggested that morphometry is an important method for biological characterization of Trypanosoma cruzi. Biometric measurements performed on the blood forms of naturally infected animals confirmed that the parasites isolated from 11 of them were within the range of the mean nuclear index (NA/NP) defined for Trypanosoma cruzi 8 . Moreover, the biometric measurements performed on the trypanosomes obtained from the circulating blood of the Balb/c mice inoculated with blood from field animals showed similar values to those of the respective wild strain.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In a recent study, Martins et al 26 suggested that morphometry is an important method for biological characterization of Trypanosoma cruzi. Biometric measurements performed on the blood forms of naturally infected animals confirmed that the parasites isolated from 11 of them were within the range of the mean nuclear index (NA/NP) defined for Trypanosoma cruzi 8 . Moreover, the biometric measurements performed on the trypanosomes obtained from the circulating blood of the Balb/c mice inoculated with blood from field animals showed similar values to those of the respective wild strain.…”
Section: Discussionmentioning
confidence: 78%
“…Solis Franco et al 6 emphasized the importance of rodents in maintaining the wild cycle of this disease. Trypanosoma cruzi has been reported to be present in more than 200 mammal species [7][8][9][10] , including some rodents dwelling in Argentina, such as Calomys musculinus 11 , Akodon dolores 12 , Calomys laucha 13 , Phyllotis griseoflavus 14 and Octodontomys gliroides 15 . The aim of this work was to investigate whether wild rodents in the central and northern regions of San Luis province, Argentina (an area of low endemicity for Chagas disease) were infected with Trypanosoma cruzi, along with the prevalence of this infection.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados apresentados nesse Q ua dro m ostram , n as diversas am ostras, v aria ções bem am plas do com prim ento total médio, larg u ra m édia do corpo e índice n u clear médio, em geral dentro dos lim ites de variação am ostrai observados por Ferriolli, B arretto & C arvalheiro (13). V erificam os valores en tre os seguintes lim ites: com pri m ento to tal m édio de 17,27/t (am ostra C .M .S .P .)…”
Section: Resultsunclassified
“…Por outro lado, a existência de correlação entre estes critérios de avaliação em um a deter m in ad a am o :tra é, ainda, aspecto passível de investigação, um a vez que h á discordân cia nos achados e interpretações dos vários Autores (3,5,6,13,14,15,19,21) que se de dicam ao assunto.…”
Section: Caracteresunclassified
See 1 more Smart Citation